2004
DOI: 10.1080/01485010490474823
|View full text |Cite
|
Sign up to set email alerts
|

INTERFERON Α-2b MAY IMPAIR TESTICULAR HISTOLOGY INCLUDING SPERMATOGENESIS IN a RAT MODEL

Abstract: Interferon-alpha has been used in various diseases at the reproductive ages. However, the effect of interferon-alpha on testicular histology has not been studied in literature. The aim of this study was to investigate the effects of interferon alpha-2B on testicular histology including spermatogenesis in a rat model. Seventeen adult male Wistar albino rats were divided into 3 groups: Six rats received 7.500 units (5 MIU/m2) of interferon alpha-2B (Intron), considered clinical treatment dose range. Six rats rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Although this strong innate immune response is likely to be critical in impairing viral replication, it may also impact upon the normal functioning of the testis. In line with this, intraperitoneal injections of IFN␣ have been shown to induce impaired spermatogenesis in rats (13), whereas in infertile men, the presence of high levels of IFN␣ was detected in the semen (14). In 1988, two transgenic studies reported sterility in male mice overexpressing IFN␣ or IFN␤ (15,16).…”
mentioning
confidence: 78%
“…Although this strong innate immune response is likely to be critical in impairing viral replication, it may also impact upon the normal functioning of the testis. In line with this, intraperitoneal injections of IFN␣ have been shown to induce impaired spermatogenesis in rats (13), whereas in infertile men, the presence of high levels of IFN␣ was detected in the semen (14). In 1988, two transgenic studies reported sterility in male mice overexpressing IFN␣ or IFN␤ (15,16).…”
mentioning
confidence: 78%
“…Two studies in rats have reported discrepant results. Hibi et al (16) found no alterations in epididymal sperm count or motility, and Ulusoy et al (17) found testicular histology modifications, but these were not related to interferon dose. On the other hand, one case report has shown azoospermia and high FSH level in a man receiving interferon (18), whereas a study in 12 patients under interferon therapy did not show any inhibin decrease (19).…”
Section: Figurementioning
confidence: 97%
“…Three slides from the upper, lower and mid portions of the testis were prepared and evaluated for each testis. The mean STD and GECT were determined in 20 seminiferous tubules of each section using a projection microscope [15], and the values were expressed in terms of micrometers (lm). Microphotographs were made using an Olympus BX 40 microscope attached to an Olympus DP12 digital camera.…”
Section: Testicular Histomorphologymentioning
confidence: 99%